مدى مساهمة معايير التدقيق الجزائرية في تحسين جودة القوائم المالية - سعيدي إشراق; عبد العزيز خليفي; بالهادف أسامة (جامعة الوادي eloued of university, 2025)
"سعت هذه الدراسة إلى تحليل مدى فعالية معايير التدقيق المعتمدة في الجزائر في تحقيق متطلبات جودة القوائم المالية، مع التركيز على دور كل من استقلالية المدقق وكفاءته المهنية في دعم مصداقية التقارير المالية. ولتحقيق هذه الأهداف، تم إعتماد المنهج الوصفي التحليلي، حيث تم الإعتماد على الاستبيان كأداة رئيسية لجمع البيانات، وجه الى عينة من المهنيين في مجال المحاسبة والتدقيق، بالإضافة إلى أكادميين من أساتذة جامعيين متخصصين في المحاسبة على مستوى ولاية الوادي، وذلك لاستطلاع ارائهم حول مدى مسامهة معايير التدقيق اجلزائرية في تحسين جودة القوائم وقد خلصت الدراسة بوضوح بأن معايير التدقيق الجزائرية تسهم إيجابيا في تحسين جودة التقارير المالية و مصداقيتها اكدت ان التطبيق المنهجي لتقييم مخاطر التحريف يساهم فعليا اكتشاف الأخطاء وتقليل فرص التلاعب المحاسبي.كما تشير إلى ان الرأي المهني المدقق يعد عاملا اساسيا في تعزيز ثقة مستخدمي المعلومات المالية. "This study aims to analyze the effectiveness of auditing standards adopted in Algeria in meeting the requirements of financial statement quality, with a focus on the role of both auditor independence and professional competence in supporting the credibility of financial reports. To achieve these objectives, the descriptive and analytical methodology was adopted. A questionnaire was used as the primary data collection tool and was directed to a sample of professionals in the fields of accounting and auditing, in addition to academic experts in accounting from El Oued province. The goal was to gather their opinions regarding the contribution of Algerian auditing standards to improving the quality of financial statements. The study clearly concluded that Algerian auditing standards contribute positively to enhancing the quality and credibility of financial reports. It confirmed that the systematic application of misstatement risk assessment effectively helps detect errors and reduce the chances of accounting manipulation. It also emphasized that the auditor’s professional judgment is a key factor in reinforcing the trust of financial information users.ماستر مالية ومحاسبية
ماستر مالية ومحاسبية
Keywords: دقيق التخارجي; جودة قوائم مالية; محافظي الحسابات; External audit; Algerian auditing standards; financial statement quality; auditors